2017
DOI: 10.1051/e3sconf/20172200015
|View full text |Cite
|
Sign up to set email alerts
|

The use of moving bed bio-reactor to laundry wastewater treatment

Abstract: Abstract. Large laboratory scale biological treatment test of industrial real wastewater, generated in industrial big laundry, has been conducted in the period of May 2016-August 2016. The research aimed at selection of laundry wastewater treatment technology included tests of two-stage Moving Bed Bio Reactor (MBBR), with two reactors filled with carriers Kaldnes K5 (specific area -800 m 2 /m 3 ), have been realized in aerobic condition. Operating on site, in the laundry, reactors have been fed real wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…The moving bed technology is not only limited to urban wastewater treatment. It can be successfully used to treat hospital wastewater, which is a major source of pharmaceuticals, in the industry to remove benzotriazoles and benzothiazoles, to purify industrial laundry wastewater, which mainly contains surfactants, to treat wastewater from the pulp and paper industry, which is characterized by high COD, BOD, and the presence of toxic chemicals, as well as in household treatment plants [ 13 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The moving bed technology is not only limited to urban wastewater treatment. It can be successfully used to treat hospital wastewater, which is a major source of pharmaceuticals, in the industry to remove benzotriazoles and benzothiazoles, to purify industrial laundry wastewater, which mainly contains surfactants, to treat wastewater from the pulp and paper industry, which is characterized by high COD, BOD, and the presence of toxic chemicals, as well as in household treatment plants [ 13 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This type of improvement usually allows for more efficient adaptation of reactors and faster achievement of the target technological performance [ 29 ]. The ecological effect of deploying AF is also associated with the reduction in secondary pollution of wastewater with chemical compounds that are used in the chemical precipitation of phosphorus with inorganic coagulants or polyelectrolytes [ 30 ]. Modified fillings can be produced from waste materials, which is in line with the assumptions of a circular economy [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another attempt was based on the utilization of biological technologies such as membrane bioreactors (MBR) [1,[12][13][14], sequencing batch reactors (SBR) [4], or moving bed bioreactors (MBBR) [15][16][17]. MBR and MBBR technologies were found to be effective in the treatment of wastewater containing detergents both when applied as a stand-alone process or as the first stage before laundry water renewal processes [1,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…MBR and MBBR technologies were found to be effective in the treatment of wastewater containing detergents both when applied as a stand-alone process or as the first stage before laundry water renewal processes [1,[18][19][20]. It was found that the laundry wastewater treated in MBBR met the quality standards required by law for wastewater discharged to surface waters [16,17]. Furthermore, it was reported that the MBR effluent could be directly reused as a process water, although only when low or medium water quality is required [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation